Estudio de probabilidades de transición radiativa hacia las capas M en Pb, Bi, Th y U - Limandri, Silvina Paola (2008)
Probabilities of radiative transitions filling M vacancies were determined for Pb, Bi, Th and U by wavelength dispersive electron probe microanalysis. Spectra were processed by means of a method for parameter refining in order to obtain the relative intensities of characteristic lines, X-ray production cross sections and transition energies.